2018
DOI: 10.2341/17-024-tr
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Toothpaste Use Against Mineral Loss Promoted by Dental Bleaching

Abstract: The toothpastes containing bioactive glass or arginine carbonate used prior to dental bleaching were effective in protecting enamel against mineral loss promoted by the whitening procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 35 publications
1
37
0
4
Order By: Relevance
“…The number of strokes was based on 1-month simulation of normal toothbrushing. 18 As both charcoal and CP's manufacturers stipulate 2 weeks of treatment, 412 cycles were performed for COAL, RT, and WT protocols. Previous reports have indicated that longer brushing cycles diminished the volume of the enamel surface, 24 and further studies could enlighten if the same is true for charcoal-based products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of strokes was based on 1-month simulation of normal toothbrushing. 18 As both charcoal and CP's manufacturers stipulate 2 weeks of treatment, 412 cycles were performed for COAL, RT, and WT protocols. Previous reports have indicated that longer brushing cycles diminished the volume of the enamel surface, 24 and further studies could enlighten if the same is true for charcoal-based products.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens of each treatment group were attached to a mechanical brushing machine (MSet, Nucci ME, São Carlos, SP, Brazil) with the enamel surface positioned upwards. Forty-hundred and twelve brushing cycles (824 strokes) were performed to simulate 14-day brushing with a frequency of 5 Hz and under a load of 200 g. 18 KCl, pH 7.0) at 37 C, 19 and the solution was renewed every 2 days.…”
Section: Brushing Protocolmentioning
confidence: 99%
“…This treatment is considered relatively safe, effective and easy to perform [1]. Although tooth whitening is an effective treatment, adverse effects can be observed in the teeth, such as a reduction in the bond strength of restorations performed immediately after bleaching [2], increased enamel surface roughness [3] and morphological and structural alterations in the enamel [4] and dentin [5].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…These changes are attributed to hydrogen peroxide-based agents that modify the organic and inorganic composition of the enamel [4]. Some remineralizing components, such as fluoride, calcium, amorphous calcium phosphate and hydroxyapatite are used to minimize adverse effects of bleaching treatments on the enamel [6].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…The reaction products are lower in molecular weight when compared to the original stain molecule, and these properties make the products easier to remove from the dental structure (7). Regardless of the technique and bleaching agent employed, adverse effects have been reported, to include: tooth sensitivity (8); changes in surface morphology; and changes to the physical-chemical properties of the dental hard tissues such as an increase in enamel roughness, a decrease in surface microhardness, and an alteration in mineral content (9)(10)(11)(12)(13). Some remineralizing compounds, such as fluoride, calcium, bioactive glass, arginine/calcium carbonate, and nanohydroxyapatite; have been investigated to minimize these adverse effects (10,12,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%